2017
DOI: 10.1057/s41299-017-0034-3
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Reputation Past and Future: A Review and Integration of Existing Literature and a Framework for Future Research

Abstract: The concept of corporate reputation is steadily growing in interest among management researchers and practitioners. In this article, we trace key milestones in the development of reputation literature over the past six decades to suggest important research gaps as well as to provide contextual background for a subsequent integration of approaches and future outlook. In particular we explore the need for better categorised outcomes; a wider range of causes; and a deeper understanding of contingencies and modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 201 publications
6
57
0
3
Order By: Relevance
“…Corporate reputation was seen to have a highly significant relationship to purchase intention of innovative food products. Studies in corporate reputation has confirmed the consumer's value the trust and reliability of the brand and corporate in a larger scale (Money et al, 2017). This research supports the argument that corporate reputation do have a higher value addition in the minds of the consumers to insist final action like purchase intention.…”
Section: Theoretical Implicationssupporting
confidence: 76%
“…Corporate reputation was seen to have a highly significant relationship to purchase intention of innovative food products. Studies in corporate reputation has confirmed the consumer's value the trust and reliability of the brand and corporate in a larger scale (Money et al, 2017). This research supports the argument that corporate reputation do have a higher value addition in the minds of the consumers to insist final action like purchase intention.…”
Section: Theoretical Implicationssupporting
confidence: 76%
“…As in other comprehensive review manuscripts (e.g. Money et al , 2017; Walker, 2010), and given the conceptual overlap when defining corporate reputation, we also included related terms such as corporate image, corporate identity and legitimacy.…”
Section: Methodsmentioning
confidence: 99%
“…Our study aims to test the SED-reputation relationship with the implementation of a double conceptual model, namely, Models A and B, although comparatively the number of studies supporting the first model is higher, being the major stream. Drivers and consequences of corporate reputation constitute a contemporary research gap, as Money et al (2017) state. In this line, after a literature review from the past decade, these authors propose a framework for future researchers in which both perspectives are integrated in a causes-consequences model for reputation.…”
Section: State Of the Art And Research Frameworkmentioning
confidence: 99%